Answer:
(-6, 6)
x=-6, y=6
Explanation:
The easiest way to solve for this is by substitution. This means substituting y with -5x-24 in the first equation. It gives you the same variables and is easy to work with.
1. Set up your equation: -7x-4(-5x-24)=18
2. Use the distribution property: -7x+20x+96=18
3. Add like terms: 13x+96=18
4. Subtract 96 from both sides: 13x=-78
5. Divide by 13 to get x alone: x=-6
Now that we have x, we can find y much easier by plugging in -6 for x.
1. Set up your equation: -5(-6)-24=y
2. Multiply: 30-24=y
3. Subtract: 6=y
Check your answers!
-7(-6)-4(6)=18
-5(-6)-24=6
There you go! Hope this helped :)